APLIKASI METODE BOUCHERI UNTUK MENGAWETKAN BAMBU SEGAR - Pipin Permadi; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1995)
This paper deals with reseach results on bamboo preservation using boucherie method. Two bamboo species,  namely andong (Gigantocloa verticillta Munro) and tali  (Gigantochloa apus Kurtz) were treated freshly using Borax (Na2B4O7. IOH2O)  solution with strenght solution of 5% as preservative. One of butt of the 8 length bamboo was immersed 10 cm in borax solution for 2. 4. 6, 8.  and  10  days and  the penetration of preservative were observed. The results showed  that  the  penetration  of  preservative  in  andong  bamboo for 2. 5, 6,  8,  and 10 consecutively  were 131,40 cm, 304,92 cm, 308.42 cm, 469,88  and 315,28 cm, while  in tali, bamboo  were 68,30 cm,  116.83   cm, 141,88 cm  and 128,17 cm,  respectively.  Maximum pnetration of preservative was achived in 8 days immersion for andong and 6 days tali.